Strategi Kepala Sekolah untuk Meningkatkan Mutu Satuan Pendidikan di SMPN 26 Sijunjung - Yenti, Desmy; Hendriani, Suswati (Universitas PGRI Semarang, 2024)
The aim of this research is to determine the leadership strategy carried out by the Head of SMPN 26 Sijunjung to improve the quality of the educational unit. The method of this research is qualitative research where data is obtained from interviews and direct observation. The Head of SMPN 26 Sijunjung's strategy for improving the quality of the educational unit is the head the school as a transformational leader, the principal acts as an agent of change, a leader in formulating a clear and structured school vision and mission and the principal as a manager. From the research results we can conclude that a less strategic school location will not affect the development of the quality of the educational unit if led by a school principal who has the right strategy in leading the educational unit.